Opportunities for a population-based cohort in Belgium - Nienke Schutte; Marlies Saelaert; Petronille Bogaert; Karin De Ridder; Herman Van Oyen; Johan Van der Heyden; Brecht Devleesschauwer (BMC, 2022)
Abstract Population-based cohorts allow providing answers to a wide range of policy-relevant research questions. In Belgium, existing cohort-like initiatives are limited by their focus on specific population groups or specific topics, or they lack a true longitudinal design. Since 2016, consultations and deliberative processes have been set up to explore the opportunities for a population-based cohort in Belgium. Through these processes, several recommendations emerged to pave the way forward - i.e., to facilitate the establishment of administrative linkages, increase digitalisation, secure long-term financial and organisational efforts, establish a consortium of the willing, and identify and tackle ethical and legal bottlenecks. This comment summarizes these recommendations, as these opportunities should be explored in depth to consolidate the existing collaborations between different stakeholders, and refers to current initiatives that can further facilitate the establishment of a Belgian population-based cohort and, more generally, administrative and health data linkage and reuse for research and policy-making.